Aesthetic Delusions: An Investigation into the Role of Rapid Visual Adaptation in Aesthetic Practice - Goldie K; Cumming D; Voropai D; Mosahebi A; Fabi SG; Carbon CC (Dove Medical Press, 2021)
Kate Goldie, 1 David Cumming, 2, 3 Daria Voropai, 1 Afshin Mosahebi, 4, 5 Sabrina Guillen Fabi, 6, 7 Claus-Christian Carbon 8, 9 1European Medical Aesthetics, London, UK; 2Oxford AI Ltd, Oxford, UK; 3Swinburne University of Technology, Melbourne, Australia; 4Division of Surgery & Interventional Science, Faculty of Medical Sciences, University College London, London, UK; 5Department of Plastic Surgery, Royal Free Hospital, London, UK; 6Cosmetic Laser Dermatology, San Diego, CA, USA; 7University of California, San Diego, CA, USA; 8Department of General Psychology and Methodology, University of Bamberg, Bamberg, Germany; 9Research Group EPÆ;G (Ergonomics, Psychological Æ;sthetics, Gestalt), Bamberg, GermanyCorrespondence: Kate GoldieEuropean Medical Aesthetics, Harley St, London, UKTel +44 7760629259Email kate@medicsdirect.comBackground: To date, the process of adaptation in the setting of aesthetic medicine has not been investigated. The combination of complex advanced feedback in the current intense social media milieu, in conjunction with easily accessible and effective aesthetic treatments, has produced pockets of overtreated patients and over-zealous practitioners. We examine whether aesthetic assessments of attractiveness and what appears natural can be distorted by the cognitive process of adaptation.Methods: Forty-eight female participants were exposed to photographs of female faces in whom lip fullness had been strongly under- or over-exaggerated, while remaining within the bounds of natural appearing lips. Before and after evaluation of the exaggerated images, participants were asked to rate an alternative set of faces in terms of attractiveness (reflecting direct assessment of effective beauty impression) and naturalness (reflecting indirect assessment of beauty norms). The evaluation set consisted of six base faces that had been digitally altered to create a systematically varying 11 step set of lip sizes from extremely thin, to the original version, to very full.Results: Second-order polynomial fits indicated clear shifts of the subjects’ facial aesthetic assessments towards the specific lip fullness of the adaptors. In contrast, such adaptions were not found for ratings of face naturalness. In contrast to research demonstrating mathematical foundations and unchanging rules governing perceptions of beauty, we show that simple viewing of exaggerated feature morphologies can rapidly result in recalibration of a person’s assessment of attractiveness.Conclusion: This paper provides evidence that facial attractiveness is fluid, and that there are psychological mechanisms that cause an aesthetic bias. Over-exposure to exaggerated features can lead to significant changes to a person’s ideas of attractiveness.Keywords: aesthetic assessments, attractiveness, standards, norm, flexibility, adaptation, facial attractiveness